Global, regional, and national burden of non-rheumatic valvular heart disease and Its projections to 2035: comprehensive analysis of the global burden of disease study 2019 - Ying, Tao; Nie, Qiong; Yan, Wei; Wang, Han; Wu, Jing (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveValvular heart disease has attracted global attention as the next heart epidemic. However, the control effect of non-rheumatic valvular heart disease (NRVHD) is not ideal. We systematically and comprehensively assessed the epidemiological information and attributable risk factors of NRVHD from 1990 to 2019, and projections by 2035.MethodsData on NRVHD were from the Global Burden of Disease (GBD) 2019. We analyzed the disease burden by age, sex, and socio-demographic index (SDI) regions from 1990 to 2019 using the Joinpoint regression model. We calculated attributable mortality and disability-adjusted life years (DALYs) associated with potential risk factors using a comparative risk assessment. Additionally, Nordpred age-period-cohort analysis predicted the NRVHD burden for the next 15 years.ResultsFrom 1990 to 2019, incident, prevalent, and death cases, and DALYs of NRVHD gradually increased globally. The age-standardized incidence (ASIR) and prevalence rate (ASPR) of NRVHD continued to increase, while age-standardized mortality (ASMR) and DALYs rate (ASDR) gradually decreased. Subgroup analysis stratified by age, sex, and SDI regions suggested: (1) The global burden of NRVHD in women is generally decreasing. (2) In people older than 55 years, ASPR and ASIR continued to increase with aging, but the decline of ASMR and ASDR was relatively flat. (3) Despite an overall decline in ASMR and ASDR, the disease burden of NRVHD was highest in high SDI regions. High systolic blood pressure was the most prominent risk factor for NRVHD, with much higher mortality and DALYs than the high-sodium diet and lead exposure. The Nordpred age-period-cohort analysis demonstrated that ASIR (20.28 per 100,000 population) is on an upward trend, and ASMR (2.06 per 100,000 population) and ASDR (33.74 per 100,000 population) are on a downward trend in the next 15 years.ConclusionThe global burden of NRVHD remains high, especially among older adults and men in high SDI areas. However, ASMR and ASDR have declined for nearly 10 years and will likely continue to do so for the next 15 years. This suggests that current medical interventions and hypertension control strategies have been effective in reducing the NRVHD burden.